Peningkatan Literasi Digital Siswa melalui Pembelajaran Menulis Surat Resmi menggunakan Surel (Email) pada Pelajaran Bahasa Indonesia Kelas V MI Mutiara Imam Asy-Syafi’I (Penelitian Tindakan Kelas) - Hasinah Putri Bahrudin; Lailil Aflahkul Yaum; Bhennita Sukmawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study was motivated by the low digital literacy skills of students, particularly in using email for formal communication, understanding email features, and sending digital documents. This research aims to improve the digital literacy skills of fifth-grade students through the implementation of email-based learning in writing formal letters. The study employed Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The participants were fifth-grade students of MI Mutiara Imam Asy-Syafi’I. Data were collected through observation, tests, and documentation, then analyzed descriptively based on the reflection results of each cycle. The findings showed that the use of email in formal letter-writing activities effectively improved students’ digital literacy skills across all observed indicators. The number of students achieving a very good digital literacy level increased from 3 students in the first cycle to 17 students in the second cycle, while students with low performance decreased from 11 students to none. These results indicate that integrating email into learning activities provides a meaningful experience in developing students’ technological skills and digital communication abilities.